Foundation Maths / Fifth Edition - Croft Anthony; Davison Robert (Pearson, 2010)
This book has been written for students taking higher and further education courses who have not specialized in mathematics on post-16 qualifications and need to use mathematical tools in their courses. Preface, Arithmetic of Whole Numbers, Fractions, Decimal Fractions, Percentage and Ratio, Algebra, Indices, Simplifying Algebraic Expressions, Factorization, Algebraic Fractions, Transposing Formulae, Solving Equations, Sequences and Series, Sets, Number Bases, Elementary Logic, Functions, Graphs of Functions, The Straight Line, The Exponential Function, The Logarithm Function, Measurement, Introduction to Trigonometry, The Trigonometrical Functions and Their Graphs, Trigonometrical Identities and Equations, Solution of Triangles, Vectors, Matrices, Tables and Charts, Statistics, Probability, Correlation, Regression, Gradients of Curves, Techniques of Differentiation, Integration and Areas Under Curves, Techniques of Integration, Functions of More Than One Variable and Partial Differentiation, Solutions, Index.